PENGARUH MEDIA PEMBELAJARAN PAPAN PINTAR PEMBAGIAN TERHADAP KEMANDIRIAN SISWA KELAS 3 DI UPTD SDN KARANG ASEM - Lailiyah, Wardatul; Kusuma, Rendra Sakbana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out whether there is an influence on the level of student independence by using Smart Board Media in Mathematics subjects for class III division material at UPTD SDN Karang Asem with this quantitative research. The research design used is a pre-Experimental Designs design. The sample used by class students III as many as 21 students in total. The instrument used is a learning independence questionnaire. Meanwhile, the analysis tests are validity, reliability and paired sample t-test tests with the help of the IBM SPSS v21.0 application. This is proven by the use of smart board media. The level of student learning independence obtained a significant value (2-tailed) of 0.000 <0.05, which states that there is a difference in the level of student learning independence using smart board media.